GC-FID method for high-throughput analysis of residual solvents in pharmaceutical drugs and intermediates. Issue 13 (25th May 2016) - Nowak, Timothy; Graffius, Gabriel C.; Liu, Yong; Wu, Naijun; Bu, Xiaodong; Gong, Xiaoyi; Welch, Christopher J.; Regalado, Erik L.
Abstract : This approach simplifies tremendously the tedious task of residual solvent quantitation, resulting in significantly less labor, greater reliability, faster time to result and at least a 290 fold reduction in solvent consumption and hazardous waste disposal. Abstract : Gas Chromatography-Flame Ionization Detection (GC-FID) analysis for quantitation of residual solvents in drugs and synthetic intermediates is one of the most important and frequently used tests in the pharmaceutical industry. However, as currently practiced, the technique requires significant sample preparation time, in addition to having a very poor 'green factor' (Analytical Method Volume Intensity, or AMVI). In this study, a simple and fast protocol using multi-solvent standard mixtures combined with a seven minute universal GC-FID method (using either He or H2 as carrier gas) and Empower™ data analysis is presented. We demonstrate that standard mixtures containing solvents commonly used in process chemistry workflows can be stored in crimped HPLC vials at −10 °C for at least 31 months. The 31 months stability data showed over 97% recovery for all 25 solvents, with overall relative standard deviation below 5%. Our approach simplifies tremendously the tedious task of residual solvent quantitation, resulting in significantly less labor, greater reliability, faster time to result and at least a 290 fold reduction in solvent consumption and hazardous waste disposal.